2019
DOI: 10.12784/nzcomjnl55.2019.4.27-34
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ perspectives of maternal mental health assessment and screening for risk during pregnancy

Abstract: Background: Increased maternal mental health needs are associated with an increased risk of maternal morbidity and mortality and occur more frequently during pregnancy than during the postnatal period. The implications of this antenatally for the mother, baby and family is increasingly becoming recognised and recommendations are being made for routine antenatal screening. Aim: This qualitative descriptive research study explored midwives' perceptions of maternal mental health antenatally, including screening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Determining engagement with non-pharmacological interventions in pregnancy would be informative, as there is a mismatch between those taking an antidepressant in pregnancy (<5%) and the reported prevalence of depressive symptoms (12%). 4 Although midwives do assess antenatal mental health informally, 38…”
Section: F I G U R E 3 Antidepressant Exposure Trajectories For Individual Pregnancies Ending In a Delivery And Those Not Ending In A Delmentioning
confidence: 99%
“…Determining engagement with non-pharmacological interventions in pregnancy would be informative, as there is a mismatch between those taking an antidepressant in pregnancy (<5%) and the reported prevalence of depressive symptoms (12%). 4 Although midwives do assess antenatal mental health informally, 38…”
Section: F I G U R E 3 Antidepressant Exposure Trajectories For Individual Pregnancies Ending In a Delivery And Those Not Ending In A Delmentioning
confidence: 99%
“…It also means involving women as active partners in their care, e.g., by giving them responsibility for routine aspects of care and letting them participate in decision-making, which also helps care providers when they need to be more directive [ 5 ]. Mellor, Payne and McAra-Couper [ 23 ] found that mental health services were lacking when midwives needed to refer pregnant women with mental health issues, and midwives routinely assessed women’s mental health during antenatal care in informal and not necessarily explicit ways. They were concerned about the introduction of routine universal antenatal screening without the availability of appropriate services for women with mental health issues such as anxiety [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mellor, Payne and McAra-Couper [ 23 ] found that mental health services were lacking when midwives needed to refer pregnant women with mental health issues, and midwives routinely assessed women’s mental health during antenatal care in informal and not necessarily explicit ways. They were concerned about the introduction of routine universal antenatal screening without the availability of appropriate services for women with mental health issues such as anxiety [ 23 ]. There is a need for relaxation training during pregnancy that promotes the wellbeing of mother, fetus and baby [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review found that midwives are increasingly aware of the impacts of perinatal mental health and are interested in routinely providing mental health care and support [32]. Other research has found that healthcare professionals (including midwives) can be uncomfortable providing mental health screening and psychosocial care [33,34]. Our pre implementation study [11] found Kimberley healthcare professionals were similarly ambivalent about administering a PLOS ONE psychosocial screening tool.…”
Section: Discussionmentioning
confidence: 75%